Cooperation Peculiarities Between Designers, Artists and Managers when Creating Black Ceramics Prototypes for the Market. A Case of “Baltic Patterns in Ceramics: from the Past to the Future” - Grigarienė, Neringa; Jurėnienė, Virginija (Vilnius University Open Series, 2022)
Today, contemporary design solutions require creative thinking because the original design is based on innovation and creative solutions to solve certain problems such as preservation of old traditions, cultural heritage for future generations. Design as an area of science and practical activities functions by defining specific design peculiarities. Design products in scientific literature are described as closely directly related to the process, distributed in the context of the process, ones that impact the context and alter the process further. A creative product is created when acting together with other artists and is planned for the consumer, where the globalisation of the 21st century is one of the threats to national cultures. In the meantime, the person first understands the image and terms created by the culture around him, so artists, creators of creative products, play an important role here. Cooperation is a new and inspiring means of this activity that provides power to initiate, implement and evaluate solutions that is based on not only shared responsibilities, but also partnership that strengthens communication, increases trust, empathy between organisations and satisfaction in a generally received result. Sientific problem may be raised: What are the specificities of design product development and commercialization? In realizing this problem the theoretical concept and peculiarities of design product were discussed; the stages and principles of design product development and its introduction to the market were analysed; a theoretical model of design product development was created and introduction to the market; the theoretical model was analyzed by the implementation of the project “Baltic Patterns in Ceramics: From the Past to the Future”. The methods of scientific literature systematic analysis, comparison and abstraction were employed in the research.